2012
DOI: 10.5539/ies.v5n5p173
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Learners’ Performance and Strategies When Writing Direct and Translated Essays

Abstract: The purpose of this study was to investigate ESL students' performance and strategies when writing direct and translated essays. The study also aimed at exploring students' strategies when writing in L2 (English) and L1 (Arabic). The study used a mixture of quantitative and qualitative procedures for data collection and analysis. Adapted strategy questionnaires, writing essay prompts and follow-up questions were utilized for data gathering. Thirty six university students participated in writing three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Another interesting result is that students always or usually try to make an effort to think how best to express their ideas in English that has mean percentage of 4. In line with the result, Ismail and Alsheikh (2012) also found out in their study that it is the most frequent strategy used by the students (69%) in the translated essay. However, the study revealed that the respondents are generally interfered in their translations which reach about 67%, although they have applied the same technique.…”
Section: Common Translation Strategiessupporting
confidence: 71%
“…Another interesting result is that students always or usually try to make an effort to think how best to express their ideas in English that has mean percentage of 4. In line with the result, Ismail and Alsheikh (2012) also found out in their study that it is the most frequent strategy used by the students (69%) in the translated essay. However, the study revealed that the respondents are generally interfered in their translations which reach about 67%, although they have applied the same technique.…”
Section: Common Translation Strategiessupporting
confidence: 71%